In pursuit of a balance: the regulation of conscience and access to sexual reproductive health care - Uberoi, Diya (Human rights review, 2017)
In any given society, rights are said to co-exist. When rights, however, begin to conflict, a balance must be sought. In few fields has the ability of governments to accommodate two conflicting sets of rights been so controversial as it has in the case of conscientious objection (CO) in reproductive health care. Today, states have an obligation under international law to protect the right to the freedom of thought, conscience, and religion of medical providers. They also, however, have an obligation to protect right to the highest attainable standard of health and other fundamental rights of women. Considering the extent to which CO has been invoked in the context of reproductive health care, international law recognizes limits to its use. Over the years, human rights bodies have sought to develop guidelines around CO in order to ensure the protection of women’s basic rights. While some state practices have shown to be consistent with guidelines established at the international level, some countries have struggled to provide an effective balance so as to protect women’s fundamental rights. Taking the example of countries in Latin America and Europe, this article provides an overview of the different ways states have sought to regulate CO in the medical context and the various difficulties ensued.